PENGETAHUAN PENDERITA HIPERTENSI TENTANG PENGOLAHAN OBAT TRADISIONAL UNTUK HIPERTENSI - Batubara, Khairunnisa (Program Studi Keperawatan Blora, Politeknik Kesehatan Kementerian Kesehatan Semarang, 2025)
Hypertension is the secound cardiovascular disease that most people suffer from in te world. The prevalence of hypertension in people aged18 years in indonesia is 34,1%. One alternative treatment that can be an option to lower blood presseure is herbal therapy. These plants have been widely used by the public in the treatment of hypertension. The specific aim is to determine the description of the knowledge of hypertension sufferers regarding the processing of traditional hypertension medicines. This research uses a”descriptive survey” research design and the research method is a cross section approach. The population in this study was 22 people in lubuk palas villge, the sampling technique used a saturated sampling technique where all members of the population were sampled, so the number of samples in this study was 22 people. Data collection techniqes are by means of observation, interviews, documentation, and filing out questinnaires and using categories of know and don’t know, catergory “fairly good”. The results of this research showed that the description of family knowledge about traditional medicine for hypertension was 7,4(74%) categorized as “sufficent” family knowledge. The researcher’s conclusion was that the description of family knowledge about traditional medicine for hypertension was in the “sufficient” catergory and obtained a score of 7,4 with a percentage of (74%).it was proven from the questionnaire. That they were only able to answer 7 and they were also unable to explain, explaining the questionnaire they had read. It was huped that it would be a motivation for the community to be able to guide families to know about tradisional medicine for hypertension.